Website Designing Rental Futsal At GLOBAL METRO FUTSAL Using Dreamweave 8, PHP, and SQL - Muhamad Fahmi Amirudin; Marzuki.Skom., MMSI Marzuki.Skom., MMSI (Jurnal Sistem Informasi, 2008)
The writing is about a quick profile of the ground lease is also futsal.Selainadministrators and ordering data penginputan the manufacturing use software (Software)PHP and SQL.Based on these circumstances, the authors make an application with reference to therunning procedure, the application is expected to assist in overcoming any existingproblems, to find out how biased search for futsal field via the Internet.